Modelling of neutral vacancies in forsterite mineral - Stashans, A. (2013)
Density functional theory and generalized gradient approximation have been employed to study Mg, Si and O vacancies in the Mg2SiO4 forsterite mineral. Microstructure of defect equilibrium geometries, electronic properties as well as chemical bonding in the region surrounding each one of the vacancies have been computed and discussed in detail. It is found that vacancies tend to increase covalent character of the chemical bonding for atoms situated in their vicinity independently of the type of vacancy. Nevertheless, obtained atomic distortion in the region surrounding vacancies generally obeys Coulomb electrostatic interaction law. Local energy states are found in the band-gap region due to the occurrence of vacancy-type defects. These findings are discussed in light of the available experimental data